PERFORMANCE THE BPSDM OF EAST JAVA PROVINCE IN IMPROVING THE QUALITY OF GOVERNMENT APARATURE SERVICES - Didiek Dwiyanto (DIA: Jurnal Administrasi Publik, 2020)
Indonesia's Long-Term Development Plan of 2025 resulted in The Undang-Undang Nomor 23 Tahun 2014 about Regional Government and The Peraturan Pemerintah Nomor 18 Tahun 2016 concerning Regional Apparatuses. East Java Province deems it necessary to establish regional regulations regarding the formation and arrangement of regional apparatuses, which results in the change from The Badan Pendidikan dan Pelatihan Provinsi Jawa Timur to The Badan Pengembangan Sumber Daya Manusia (BPSDM) East Java. This research uses descriptive qualitative analytic method which applies theories and concepts about public management and public services, with a focus of research on how the performance of BPSDM East Java Province in improving the quality of the State Civil Apparatus? What are the inhibiting factors and supporting performance of BPSDM East Java Province in improving the quality of the State Civil Apparatus?